1997
DOI: 10.1002/pro.5560060217
|View full text |Cite
|
Sign up to set email alerts
|

Intrachain disulfide bond in the core hinge region of human IgG4

Abstract: IgG is a tetrameric protein composed of two copies each of the light and heavy chains. The four-chain structure is maintained by strong noncovalent interactions between the amino-terminal half of pairs of heavy-light chains and between the carboxyl-terminal regions of the two heavy chains. In addition, interchain disulfide bonds link each heavy-light chain and also link the paired heavy chains. An engineered human IgG4 specific for human tumor necrosis factor-cy (CDP571) is similar to human myeloma IgG4 in tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
103
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 33 publications
6
103
0
1
Order By: Relevance
“…Under nonreducing conditions, all IgG variants electrophoresed as a single major band, as anticipated. The IgG4 variant gave rise to an additional minor band, consistent with the presence of ''half-IgG,'' as reported for other recombinant IgG4 and attributed to inefficient interheavy chain disulfide bond formation (23,24). Mutation of the IgG4 hinge sequence, CPSC, to mimic the IgG1 hinge, CPPC, creates a strong preference for interheavy over intraheavy chain disulfide bonding (23 -25).…”
Section: Generation Of Anti-cd70 Igg Variantssupporting
confidence: 60%
“…Under nonreducing conditions, all IgG variants electrophoresed as a single major band, as anticipated. The IgG4 variant gave rise to an additional minor band, consistent with the presence of ''half-IgG,'' as reported for other recombinant IgG4 and attributed to inefficient interheavy chain disulfide bond formation (23,24). Mutation of the IgG4 hinge sequence, CPSC, to mimic the IgG1 hinge, CPPC, creates a strong preference for interheavy over intraheavy chain disulfide bonding (23 -25).…”
Section: Generation Of Anti-cd70 Igg Variantssupporting
confidence: 60%
“…Interactions in both the IgG4 core hinge sequence and the IgG4 CH3 domain are critical for this process to occur (31,32). Substitution of serine with proline at position 228, as found in IgG1 and IgG2 core hinge sequences (i.e., CPSCP to CPPCP) stabilized the inter-H chain disulfide linkage in NIB(28SA)-G4-S228P with the resulting loss of half-molecules after SDS-PAGE, as shown for other IgG4 mAbs with "wild-type" hinges (10,16,33,34). Exchange of the IgG4 for the IgG1 core hinge was previously shown to abrogate Fab arm-exchange in vitro and in vivo (10,32).…”
Section: Responses Of Pbmcs To Nib(28sa)-g4 Nib(28sa)-g1 and Nib(28mentioning
confidence: 72%
“…The greater superagonistic activity of NIB(28SA)-G4-S228P in cocultures compared with the IgG4 molecules with wild-type hinges may thus be explained, at least in part, by its inability to engage in Fab arm-exchange. Conformational modeling has indicated that proline in the core hinge region allows less torsional flexibility than serine, eliminating the potential for intrachain disulfide bridge formation between the two hinge cysteines at positions 226 and 229 (33). As immobilized IgG4 mAb could not have engaged in Fab arm-exchange, the effects of restricted hinge flexibility may also have enhanced the in vitro functional activity of NIB(28SA)-G4-S228P in both functional assay formats, potentially through optimizing and stabilizing CD28 ligation and subsequent superagonistic signaling.…”
Section: Responses Of Pbmcs To Nib(28sa)-g4 Nib(28sa)-g1 and Nib(28mentioning
confidence: 99%
“…Thus, whereas replacing either of these residues in IgG4 by their IgG1 counterpart (i.e., P228 or K409) blocked FAE both in vitro and in vivo, introducing both residues enabled IgG1 molecules to engage in FAE (21). Because breaking the covalent linkage between half-molecules is a prerequisite for FAE, residue S228 (opposed to P228) is thought to act by making the interheavy chain disulfide bonds more susceptible to reducing conditions (22). Dissociation of the noncovalently associated CH3 domains has been shown to be the rate-limiting step in the FAE reaction (23) and heavily dependent on the composition of the CH3-CH3 interface residues (24).…”
mentioning
confidence: 99%